When we are happy, we are the same-emotions as a boundary condition for the impact of cultural differences on strategic decisions - Sophie Florian; Philip Meissner; Torsten Wulf; Xian Xu; Philip Yang (Schmalenbach Journal of Business Research (SBUR), 2024)
Strategic decision-making research has mainly relied on the values-based approach to culture. However, the dynamic constructivist approach to culture has shown that cultural tendencies may also be altered by contingency factors in the decision-making process itself. We theorize based on the appraisal tendency framework as well as the concept of cultural affordances that emotions, such as happiness, can alter the cultural dispositions of managers from Western and East Asian contexts. To test our hypotheses, we conduct a~lab-in-the-field experiment with 187 executives from China and Germany, and measure emotions based on participants' psychophysiological skin conductance responses. Our results show that happiness moderates and can even reverse initial cultural dispositions in executives' strategic decision-making behavior. These findings suggest that emotions may be important contingency factors that can alter the initial cultural dispositions of decision makers in the strategy process.
Keywords: 650; Cultural differences; Culture; Emotions; Strategic decision making